Strategic unknowns: towards a sociology of ignorance - McGoey, Linsey (Economy and society, 2012)
Developing an agenda for the social study of ignorance, this paper introduces the sociology of strategic unknowns: the investigation of the multifaceted ways that ignorance can be harnessed as a resource, enabling knowledge to be deflected, obscured, concealed or magnified in a way that increases the scope of what remains unintelligible. In contrast to theoretical preoccupations that underlie the study of knowledge accumulation, a focus on the importance of strategic unknowns resists the tendency to value knowledge over ignorance or to assume that the procurement of more knowledge is linked in an automatic or a linear fashion to the attainment of more social or political power. Refining and challenging the assumption that modern liberal societies inevitably thrive on the accumulation of information about the public personas, private psyches, consumer habits or political proclivities of citizens, the papers in the special issue explore how the cultivation of strategic unknowns remains a resource - perhaps the greatest resource - for those in a position of power and those subject to it.